Research of transverse dynamic oscillation for the piston in labyrinth compressor. (August 2021) - Zhang, Wenshan; Lv, Qian; Hao, Haitian; Pan, CJ; Feng, Quanke; Groll, Eckhard A.; Wu, Weifeng; Yu, Xiaoling
In labyrinth compressor, non-contact labyrinth sealing clearance was designed between piston and cylinder wall to process oil-free gas containing fine particles. To prevent the collision between piston and cylinder wall, this labyrinth clearance was usually set bigger than 2‰ of the piston diameter. Such a big clearance seriously increased the leakage rate and reduced the volume efficiency of the compressor. Thus, it was necessary to investigate the piston transverse oscillation, and find a way to minimize the oscillation amplitude to reduce the labyrinth clearance set. In this paper, a dynamic model was established to predict the piston transverse oscillation based on inertia mass vibration analysis and finite difference method. Experiments investigation of the piston transverse oscillation track showed high prediction accuracy of the proposed model. Then, structure parameters optimization of the compressor was carried out to reduce piston oscillation amplitude. It was found that ratio of the crank shaft radius to connecting rod length and the position of the guide bearing were two key parameters determining the oscillation amplitude. Finally, a case study showed that the oscillation amplitude could be reduced by 53% by adopting optimized parameters.